Learning English language and mathematics: a study on students' emotion perspective / Marina Mohamed Zahidi - Mohamed Zahidi, Marina (2012)
The aim of this study was to determine the students’ classroom emotions and homework emotions in learning English language and Mathematics. Emotion plays an important role in education. Therefore this study sought to investigate the students’ classroom emotions and homework emotions in learning English and Mathematics. This study also looked into students’ grade performance in English and Mathematics since the implementation of PPSMI and their preference in the continuation of learning Mathematics in English. 250 randomly selected form four students from two schools in the district of Petaling Perdana participated in this study. Data were collected using the survey method and were analyzed using both descriptive and inferential statistics. Based on the collected data, the findings showed that students’ have pleasant classroom emotion and homework emotion for English and Mathematics classroom learning. Furthermore, there is significant relationship between classroom emotions and homework emotions in English and Mathematics. Students also showed that they have higher pleasant Mathematics classroom and homework emotions as compared to English classroom and homework emotions. In term of determining the contribution of the significant predictor of English classroom emotions, the results revealed that English homework emotions contributed 62.6% to the variance of English classroom emotions. On the other hand, Mathematics homework emotions and Mathematics PMR grade contributed 75.4% to the variance of Mathematics classroom emotions. The findings also showed that almost all of the respondents (97.6%) prefer to continue the learning of Mathematics in English. The findings on students’ grade performance revealed that there is no declination of students’ level of achievement in UPSR and PMR for English and Mathematics since the implementation of PPSMI. The findings of this study have implications to the role of emotion in education especially in the learning of English and Mathematics. Based on the findings, this study also provides recommendations for practices and future research.